Globalization, occupational restructuring and firm performance - Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2013)
In this study, the patterns of occupational restructuring and their micro-level mechanisms are examined by applying standard measures of job and worker flows at the occupation and firm levels using longitudinal employeremployee data from the Finnish business sector for the years 2000-2006. Special attention is given to determining how global firms (i.e., multinational enterprises and offshoring firms) contribute to occupational restructuring and to establishing the role of occupational structures when explaining productivity and profitability gaps between global and local firms. The findings indicate that global firms have contributed to reshaping occupational structures, and although this contribution is clearly reflected in their productivity, it is not as clearly reflected in their profitability.The findings imply that employees have captured a dominant share of the productivity advantage of global firms.
Keywords: J24; F23; 330; globalization; offshoring; occupational restructuring; productivity; profitability